Increasing Strength of Clay Soils with the Use of Basalt Fiber: An Experimental Study - Topcuoglu, Yasemin Aslan; Gurocak, Zulfu (My University, 2024)
Due to the increase in population, the demand for buildings increases. The engineering properties of the soils on which these structures will be built may not always meet the desired conditions. In such cases, soil improvement methods are used. One of these methods is additive used stabilization, in which additives such as lime, fly ash, volcanic ash and tuff, silica fume, and blast furnace slag are used. This method has been used successfully for years. However, in recent years, interest in the use of different types of fibers has increased. Some of these fibers are glass, basalt, polypropylene, and carbon. Basalt fibers have begun to attract attention in soil reinforcement applications due to the properties of their raw material, basalt rock, which is widely distributed in nature, natural, and has high strength. In this study, the effect of basalt fiber reinforcement on the unconfined compressive strength of high plasticity bentonite clay was revealed. For this purpose, 12 mm long basalt fiber in different proportions (1%, 2%, 3%, 4%, and 5%) was used as reinforcement in bentonite clay, and the optimum fiber ratio that provided the maximum increase in strength was determined. According to the results of the study, when 12 mm long basalt fiber was used as reinforcement in bentonite clay, the maximum strength value was obtained at a 4% basalt fiber ratio. However, the strength value decreased in the sample where 5% BF was used. It has been determined that basalt fiber reinforcement improves the strength properties of bentonite clay.
Keywords: Reinforcement; Basalt fiber; unconfined compressive strength; bentonite clay